'How Time Flies': Celebrating the Universal Declaration of Human Rights in the 1960s. Issue 3 (26th May 2016) - Burke, Roland
ABSTRACT: Recent histories of human rights have identified the 1970s as the most decisive epoch in the birth of the modern rights era. These works have tended toward a parenthetic dismissal of the period 1948–70 as years of interregnum, of marginal impact to the 'breakthrough' moment which followed. This article argues for a more complex periodisation, and reclaims the importance of the 1960s. Far from an undifferentiated abyss, the two decades between the adoption of the Universal Declaration of Human Rights (UDHR) and the 1968 International Human Rights Year held their own shifts, integral to the evolution of modern human rights. A crucial transition in the status of the UDHR occurred across the mid-1960s, roughly aligned with the terminal years of liberal post-colonialism. Through a comparison of two hitherto neglected events in the history of human rights, the fifteenth and twentieth anniversary commemorations of the UDHR, in December 1963 and 1968, this article traces the trajectory of that transition. These commemorations, concentrated moments of explicit reflection on the meaning of human rights, encapsulated the gulf between the early and the late 1960s. In the space of five years, any vestigial consensus on the vision enunciated in 1948 was obliterated.